Daños causados por fitopatogenos y entomofauna asociada en Alnus acuminata H.B.K. - Garcia, M.R.=700 1 Coba de Gutierrez, B.; Acosta Gomez, A.
(En, Es)
Ilus., 15 ref.
Keywords: ALNUS ACUMINATA; DAÑOS; PATOGENOS; HONGOS; FAUNA; NEMATODOS DE INSECTOS; CICADELLIDAE; COLOMBIA; AGRONOMIA COLOMBIANA